The multidimensionality of abstract concepts: A systematic review. (August 2021) - Conca, F.; Borsa, V.M.; Cappa, S.F.; Catricalà, E.
Highlights: We reviewed behavioural, neuroimaging, and neurophysiological studies exploring abstract concepts in health and disease. The results are compatible with a categorical organization of abstract knowledge. An embodied view is suggested by the engagement of brain systems involved in the corresponding experiences. Abstract: The neuroscientific study of conceptual representation has largely focused on categories of concrete entities (biological entities, tools…), while abstract knowledge has been less extensively investigated. The possible presence of a categorical organization of abstract knowledge is a debated issue. An embodied cognition framework predicts an organization of the abstract domain into different dimensions, grounded in the brain regions engaged by the corresponding experience. Here we review the types of experience that have been proposed to characterize different categories of abstract concepts, and the evidence supporting a corresponding organization derived from behavioural, neuroimaging (i.e., fMRI, MRI, PET, SPECT), EEG, and neurostimulation (i.e., TMS) studies in healthy and clinical populations. The available data provide substantial converging evidence in favour of the presence of distinct neural representations of social and emotional knowledge, mental states and magnitude concepts, engaging brain systems involved in the corresponding experiences. This evidence is supporting an extension of embodied models of semantic memory organization to several types of abstract knowledge.